Estimation of thumb-muscle length by ultrasound on portable thumb training system - Sidek, Shahrul Na'im; Roslan, Muhammad Rozaidi; Sidek, Sabrilhakim; Mohd Khalid, Mohd Syukry (IEEE, 2017)
Human limb amputation following severe injuries or bacterial infection caused by accidents, vascular diseases and diabetes has significant impact to the well-being of a person. Limb amputation is usually replaced by prostheses to restore the look of the limb as well as the basic function of the missing limb that can assist patient on activities of daily living. Improvement on robotic prostheses in these aspects has been done extensively in the previous decade. The focus on current prostheses development is to use electromyography (EMG) signals in myoelectric control of the system through analyzing the remaining signal generated from the nerves or muscles left after amputation. Hill’s muscle model requires both EMG signals and muscle length information to predict force that is produced at contact point. In this paper, the measurement of the muscle length using ultrasound imaging and magnetic resonance imaging (MRI) using a well-designed portable thumb training system is described. The measurement done using ultrasound image is compared to the pre-measurement done by MRI in order to establish a set of references. The thumb training system is designed to allow the thumb to flex to range of degrees that have been defined in this research work. The result from the ultrasound imaging shows good accuracy in measuring thumb muscle length and thus allows the research work to proceed to model thumb-tip force based on Hill’s muscle model.